Технології дистанційного навчання на післядипломному етапі професійного розвитку фахівців фармації - Авраменко, Микола Олександрович; Ткаченко, Наталя Олександрівна; Рябоконь, Юрій Юрійович; Бігдан, Олексій Антонович; Avramenko, M. O.; Tkachenko, N. O.; Riabokon, Yu. Yu.; Bigdan, O. A.; Авраменко, Н. А.; Ткаченко, Н. А.; Рябоконь, Ю. Ю.; Бигдан, А. А. (Запорізький державний медичний університет, 2021)
Фармацевтична освіта має гнучко, динамічно та адекватно реагувати на суспільні трансформації шляхом продукування нових освітніх послуг, технологій навчання та організації освітнього процесу. У відповідь на запит часу післядипломна професійна освіта прагне відповідати потребам сьогодення: сформувалася нова концепція підвищення ефективності освіти та професійного рівня фахівців – навчання впродовж життя, яке неможливе без використання інформаційно-комунікаційних технологій. Мета роботи – показати особливості організації освітнього процесу фармацевтичних фахівців на післядипломному етапі в Запорізькому державному медичному університеті (ЗДМУ) та окреслити його проблемні питання з визначенням можливих шляхів удосконалення в контексті безперервного професійного розвитку (БПР). Матеріали та методи. Матеріал для дослідження – досвід організації навчання провізорів-інтернів, слухачів циклів підвищення кваліфікації на факультеті післядипломної освіти ЗДМУ за останні 10 років, звітна й інша облікова документація, нормативно-правові акти щодо вищої фармацевтичної освіти різних управлінських рівнів. Використали методи аналізу, синтезу, групування, дедукції, логіки й узагальнення. Результати. Післядипломний етап БПР фармацевтичних фахівців спрямований на вдосконалення професійних компетентностей і дає змогу фахівцеві підтримувати або покращувати стандарти професійної діяльності відповідно до потреб сфери охорони здоров’я. Підготовка фармацевтичних фахівців на факультеті післядипломної освіти відбувається в очно-дистанційному форматі з використанням технологій дистанційного навчання у спеціалізованому вебсередовищі, що створене на основі сучасних психолого-педагогічних та інформаційно-комунікаційних технологій (базовим є пакет Microsoft Office 365 програми Teams, Skype for business тощо). Такий формат навчання стимулює здобувачів освіти до розкриття свого потенціалу, підвищення рівня самоорганізації та самоменеджменту, поглиблює професійні компетентності шляхом удосконалення комунікаційної складової. Керівництво ЗДМУ на засадах соціальної відповідальності постійно працює над підвищенням якості освітніх послуг, зокрема на післядипломному етапі. Висновки. За результатами критичного аналізу досвіду організації навчання провізорів-інтернів, слухачів циклів підвищення кваліфікації на ФПО ЗДМУ за останні 10 років, звітної та нормативно-правової документації визначили особливості організації освітнього процесу фармацевтичних фахівців на післядипломному етапі, окреслили його проблемні питання та з’ясували шляхи їх вирішення в контексті БПР. Today, pharmaceutical education has to respond flexibly, dynamically and adequately to social transformations by developing new educational services, teaching technologies and organizing the training process. In response to the demand of the time, postgraduate professional education strives to meet the current needs; a new concept of increasing the effectiveness of education and the professional level of specialists has been formed: lifelong learning is impossible without the use of information and communication technologies. The aim of the work is to identify the features of the organization of the training process of pharmaceutical professionals at the postgraduate stage at Zaporizhzhia State Medical University (ZSMU) and to outline its problematic issues with further identification of possible ways of improvement in the context of continuing professional development (CPD). Materials and methods. The study was grounded on the experience of organizing the training of pharmaceutical interns, students of advanced training cycles at the Faculty of Postgraduate Education of ZSMU for the last 10 years, reporting and other accounting documents, regulations on higher pharmaceutical education at various levels. The methods of analysis and synthesis, grouping, deduction, logic and generalization are used in the work. Results. The postgraduate phase of СPD of pharmaceutical specialists is aimed at improving professional competencies and allows the specialist to maintain or improve the standards of professional activity in accordance with the needs of health care. Training of pharmaceutical specialists at the Faculty of Postgraduate Education is practiced both face-to-face and distantly, using distance learning technologies in a specialized web environment, grounding on modern psychological, pedagogical and information and communication technologies (basic is Microsoft Office 365 and others). This format of education stimulates students to unleash their potential, increase the level of self-organization and self-management, deepens professional competencies by improving the communication component. The management of ZSMU, driven by social responsibility, constantly works on improving the quality of educational services, including those of the postgraduate stage. Conclusions. According to the results of critical analysis of the experience of training pharmaceutical interns and students of advanced training cycles at FPE of ZSMU for the last 10 years, reporting and regulatory documentation, features of the educational process of pharmaceutical specialists at the postgraduate stage are identified, its problematic issues are outlined and ways to solve them in the context of СPD are deteermined. Фармацевтическое образование должно гибко, динамично и адекватно реагировать на общественные трансформации путем выработки новых образовательных услуг, технологий обучения и организации образовательного процесса. В ответ на запрос времени последипломное профессиональное образование стремится соответствовать потребностям современности: сформировалась новая концепция повышения эффективности образования и профессионального уровня специалистов – обучение в течение жизни невозможно без использования информационно-коммуникационных технологий. Цель работы – обозначить особенности организации образовательного процесса фармацевтических специалистов на последипломном этапе в Запорожском государственном медицинском университете (ЗГМУ) и определить его проблемные вопросы и возможные пути совершенствования в контексте непрерывного профессионального развития (НПР). Материалы и методы. Материал для исследования – опыт организации обучения провизоров-интернов, слушателей циклов повышения квалификации на факультете последипломного образования ЗГМУ за последние 10 лет, отчётная и другая учётная документация, нормативно-правовые акты относительно высшего фармацевтического образования различных управленческих уровней. В ходе работы использованы методы анализа и синтеза, группировки, дедукции, логики и обобщения. Результаты. Последипломный этап НПР фармацевтических специалистов направлен на совершенствование профессиональных компетенций и позволяет специалисту поддерживать или улучшать стандарты профессиональной деятельности в соответствии с потребностями здравоохранения. Подготовка фармацевтических специалистов на факультете последипломного образования проходит в очно-дистанционном формате с использованием технологий дистанционного обучения в специализированной веб-среде, созданной на основе современных психолого-педагогических и информационно-коммуникационных технологий (базовым является пакет Microsoft Office 365 программы Teams, Skype for business и др.). Такой формат обучения стимулирует соискателей образования к раскрытию своего потенциала, повышению уровня самоорганизации и самоменеджмента, углубляет профессиональные компетентности за счёт совершенствования коммуникационной составляющей. Руководство ЗГМУ, базируясь на принципах социальной ответственности, постоянно работает над повышением качества образовательных услуг, в том числе на последипломном этапе. Выводы. По результатам критического анализа опыта организации обучения провизоров-интернов, слушателей циклов повышения квалификации на ФПО ЗГМУ за последние 10 лет, отчётной и нормативно-правовой документации установлены особенности организации образовательного процесса фармацевтических специалистов на последипломном этапе, определены его проблемные вопросы и пути их решения в контексте НПР.
Distance learning technologies at the postgraduate stage of professional development of pharmacists
Технологии дистанционного обучения на последипломном этапе профессионального развития специалистов фармации
Авраменко М. О. - ORCID ID: 0000-0002-4268-5947; Ткаченко Н. О. - ORCID ID: 0000-0002-8566-5938; Рябоконь Ю. Ю. - ORCID ID: 0000-0002-2273-8511; Бігдан О. А. - ORCID ID: 0000-0002-2283-1695.
Keywords: фармацевтична освіта; безперервний професійний розвиток; технології дистанційного навчання; pharmaceutical education; continuous professional development; distance learning; фармацевтическое образование; непрерывное профессиональное развитие; технологии дистанционного обучения